2007
DOI: 10.1021/ja068511u
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic β-Sheet Peptides That Mimic Protein Quaternary Structure through Intermolecular β-Sheet Interactions

Abstract: This paper reports the design, synthesis, and characterization of a family of cyclic peptides that mimic protein quaternary structure through β-sheet interactions. These peptides are 54-membered-ring macrocycles comprising an extended heptapeptide β-strand, two Hao β-strand mimics [JACS 2000, 122, 7654] joined by one additional α-amino acid, and two δ-linked ornithine β-turn mimics [JACS 2003, 125, 876]. Peptide 3a, as the representative of these cyclic peptides, contains a heptapeptide sequence (TSFTYTS) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
82
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 80 publications
(59 reference statements)
4
82
0
1
Order By: Relevance
“…These proteins form amyloid-like oligomers and fibrils and exhibit cytotoxicity. Our previous studies showed that macrocyclic peptides form oligomers in solution (36) and mimic amyloid oligomers for structural studies (37). Here, we find that, on incubation at 37°C for 0.5 h, BAMs form amyloid-like oligomers that are recognized by A11, the polyclonal amyloid-oligomer-specific conformational antibody (Fig.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…These proteins form amyloid-like oligomers and fibrils and exhibit cytotoxicity. Our previous studies showed that macrocyclic peptides form oligomers in solution (36) and mimic amyloid oligomers for structural studies (37). Here, we find that, on incubation at 37°C for 0.5 h, BAMs form amyloid-like oligomers that are recognized by A11, the polyclonal amyloid-oligomer-specific conformational antibody (Fig.…”
supporting
confidence: 55%
“…S4A). Diffusion coefficients of BAMs (Aβ [30][31][32][33][34][35][36] ) measured by NMR confirmed that they self-associate in solution at millimolar concentrations, consistent with the formation of BAM oligomers. (Fig.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…One approach targeted amyloid fibrils by computationally designing a peptide to form a terminating β-strand on a growing fibril (28). Another study took the sequence of the β-strand of a known β-strand mediated homodimer and embedded it in a cyclic peptide (29). A crystal structure of the peptide showed it formed an antiparallel β-strand paired dimer as predicted (30).…”
mentioning
confidence: 99%